2020
DOI: 10.1111/srt.12854
|View full text |Cite
|
Sign up to set email alerts
|

Application and challenge of reflectance confocal microscopy in the diagnosis of pigmented nevus

Abstract: Pigmented nevus is a benign tumor composed of nests of melanocytes. From infants to the elderly, almost everyone has it. It can grow in any part of normal people. Based on different locations of melanocytes in the skin, pigmented nevus can be classified into junctional nevus, compound nevus, and intradermal nevus. Some grow on the head and face or the limbs which affect the appearance, while some grow in such friction-prone parts as the palm, sole, neck or back. If the pigmented nevus increases significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The diagnosis of condyloma is particularly challenging under RCM because koilocytes, which are the most relevant feature for the diagnosis, can be difficult to recognize. Koilocytes appear in the granular layer or the spinous layer, larger than normal skin keratinocytes with possible large nucleus, and the cytoplasm has a low refractive index [ 9 ]. A recent study on 75 patients with histologically proven genital warts found 36% false positive and 21% false negative results based on RCM [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of condyloma is particularly challenging under RCM because koilocytes, which are the most relevant feature for the diagnosis, can be difficult to recognize. Koilocytes appear in the granular layer or the spinous layer, larger than normal skin keratinocytes with possible large nucleus, and the cytoplasm has a low refractive index [ 9 ]. A recent study on 75 patients with histologically proven genital warts found 36% false positive and 21% false negative results based on RCM [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Koilocytes appear in the granular layer or the spinous layer, larger than normal skin keratinocytes with possible large nucleus, and the cytoplasm has a low refractive index [ 9 ]. A recent study on 75 patients with histologically proven genital warts found 36% false positive and 21% false negative results based on RCM [ 9 ]. Misdiagnosis and missed diagnosis included bowenoid papulosis and squamous cell carcinoma in situ, which can have similar histologic features.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 390 patients with clinically suspicious SK, dermatologists using RCM could not diagnose SK in 25% of participants [120]. SKs have previously been misdiagnosed as pigmented nevi, and RCM features have been reported as insufficient for distinguishing melanoacanthoma from melanoma [121][122][123].…”
Section: Other Optical Techniquesmentioning
confidence: 99%
“…Many studies have reported that RCM was not only applied to diagnose skin mycosis but also nail and hair dermatophytosis [10,11]. Moreover, due to its advantages of painless, real time and convenience, [12] it has been used to detect inflammatory skin diseases, pigmented skin diseases, infectious skin diseases and skin tumors [13][14][15]. At present, it is not well known whether it can be applied to diagnose dermatomycosis independently and what is the potential diagnostic accuracy on dermatomycosis [16].…”
Section: Introductionmentioning
confidence: 99%